Concentration of Zn, Cu and Pb in some selected marine fishes of the Pahang coastal waters, Malaysia - Yunus, Kamaruzzaman; Ong, Meng Chuan; Zabri, Rina Sharlinda (Science Publications, 2010)
Problem statement: Heavy metals constitute one of the most hazardous substances that could be accumulated in biota. Fish populations exploited by man often live in coastal area environments that contain high levels of heavy metals, coming from human activities such as industrial and agricultural wastes. A problem to deal when using fishes as biomonitors of heavy metals is the relationship existing between metal concentration and several intrinsic factors of the fish such as organism size, genetic composition and age of fish. Approach: Concentration of Zn, Cu and Pb were determined in eight commercially valuable fish species, Selaroides leptolepis, Euthynnus affinis, Parastromateus niger, Lutjanius malabaricus, Epinephelus sexfasciatus, Rastrelliger kanagurta, Nemipterus japonicus and Megalaspis cordyla from Pahang coastal water. The concentration was measured by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The study focuses on the level of Zn, Cu and Pb in order to assess the environmental pollution by using fishes as an indicator. Results: Concentrations of the heavy metals in examined fish species ranged as follow: Zn 19.27 µg g-1 dry weight; Cu 2.88 µg g-1 dry weight and Pb 0.26 µg g-1 dry weight, respectively. The concentrations of Zn, Cu and Pb were found to follow the order: stomach > muscle > gills. Significant correlations were found between fish weight and heavy metals concentration in the fish organs. Conclusion: The estimated values of all metals in muscles of fish in this study were below the established values. Therefore, it can be concluded that the fish from Pahang coastal water are comparatively clean and do not constitute a risk for human health.